Systematic Literatur Review: Pengaruh Pembelajaran Daring Terhadap Minat Belajar Siswa Sekolah Dasar Pada Masa Pandemi Covid-19 - Nabila Siti Khoirunnisa; Sayyidatul Munnah; Intan Suryaningsih; Muhammad Gilang Ramadhan; Fina Fakhriyah; Erik Aditia Ismaya (Universitas Muhammadiyah Kuningan, 2023)
The purpose of this study was to determine the effect of online learning on the learning interest of elementary school students during the Covid-19 pandemic. This research uses the systematic literature review (SLR) method which aims to examine the literature on the effect of online learning on students' learning interest during the Covid 19 pandemic. Teaching in elementary schools in this study is all the time with parental guidance. Students study online via whatsapp and collect assignments directly. The results of this study indicate that online learning during the Covid-19 pandemic has affected various aspects of students, including the level of thinking, communication skills, technological abilities has decreased, this is due to a lack of parental guidance and the facilities they have. have is the reason for this not optimal.